Back-analysis of the Bingham Canyon Mine southeast wall: a complex slope failure mechanism called Leo - Ergun, S; Cambio, D; Williams, CP; Gaida, M; Lawrence, K; Katsaga, T; Lorig, L; Weigel, J; Gibbs, J; Chapin, G; Peik, B; Sankhaneel, S (SSIM 2023: Third International Slope Stability in Mining Conference, 2023)
In May 2021, Rio Tinto’s Bingham Canyon Mine (BCM) experienced a 19 Mt slope collapse referred to as the ‘Leo’ failure. Early detection of the initial slope movement and prediction of the collapse by BCM’s integrated monitoring systems allowed for safe evacuation of the mine staff and equipment. Datasets collected prior to and during the failure provide an opportunity to study the progression and dynamics of the collapse. Two independent consultants with extensive prior experience at BCM were engaged to expand the understanding and interrogate the sequence of events leading to the Leo failure through back-analysis in FLAC3D® software (Itasca Consulting Group 2020). The objective of the study was to determine mechanisms and develop learnings that could be used to identify and mitigate similar scale inter-ramp failures as future mine pushbacks are evaluated. The consultants each adopted slightly different approaches in characterisation and modelling processes and operated independently under the direction of mine personnel so that findings could be evaluated with reduced bias. Both consultants were successful in achieving the back-analysis requirements set forth. There were many similarities between the final calibrated models. Learnings identified by both teams during the process were shared. Key differences remain between the two successful back-analyses which results in a measure of uncertainty in the understanding of the observed wall response during the failure. This paper outlines the conceptual failure mechanism and definition of calibration targets and describes the independent back-analyses performed by each consultant. By engaging a collaborative team, Rio Tinto was able to achieve a more robust and reliable means to assess current operational decisions and the future mining pushbacks.
Keywords: back-analysis